Mergers and Acquisitions Integration and Transformation Management as the Gateway to Success - Bergamin, Stephan (Management for Professionals,, 2018)
This book brings home the message that meticulous integration management is the key to success in M&A transactions. Half of all M&A transactions are unsuccessful because many companies embarking on a merger neglect this key success factor. Based on 30 years of experience of corporate mergers and acquisitions as well as the subsequent implementation of growth strategies, the authors have developed a practical manual that helps managers optimize and streamline their growth strategy using persistent integration and transformation management. The book provides first-hand accounts of M&A transactions that the authors led or were involved in, assessing each case from an insider perspective and outlining the key success factors and pitfalls. It concludes with practical checklists including the most relevant topics for each individual step toward successful integration.